Community Health Promotion Program: Evaluating the Impact of Health Interventions in the Community - Arlia, Arlia; Massaguni, Masnita; Ambarwati, Eny Retna; Multazam, Andi Muhammad; Renaldo, Nicholas (International Journal of Community Service (IJCS), 2025)
Community health promotion programs are essential for improving public health outcomes by addressing both individual behaviors and environmental determinants. This study evaluates the impact of a community-based health intervention implemented in Indonesia, focusing on changes in health behaviors, risk factors, and community engagement. A mixed-methods approach was employed, combining quantitative data from pre- and post-intervention health screenings and self-report surveys with qualitative insights gathered through focus groups and interviews. The intervention targeted middle-aged adults at risk of cardiovascular disease, involving ten group sessions facilitated by trained community health workers. Quantitative results demonstrated significant improvements in body weight, blood pressure, smoking cessation, and physical activity, with 30% of participants achieving the intended reduction in cardiovascular risk factors. Qualitative findings highlighted increased community awareness, sustained behavioral changes, and the importance of cultural appropriateness and ongoing support. The study underscores the effectiveness of community engagement and robust evaluation frameworks in health promotion initiatives. Challenges included ensuring broad participation and addressing adverse selection. The results support the continued investment in community-based health interventions and emphasize the need for ongoing evaluation and adaptation to maximize impact and sustainability. This research contributes to the growing body of evidence on the value of participatory, culturally sensitive health promotion strategies in diverse settings.